Stakeholder Awareness and Acceptance of the Revised VMDGCV of NVSU: Basis for Institutional Engagement in the EE Program - Nebrida, Alan P.; Quidit, Cherry D.; Natividad, Jemimah P.; Nebrida, Joan Minia; Soriano, Dhom Ryan S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The Vision, Mission, Developmental Goals, and Core Values (VMDGCV) define the strategic orientation and identity of higher education institutions. In technical fields like Electrical Engineering (EE), adherence to these institutional statements guarantees program relevance, stakeholder involvement, and preparedness for accreditation. This research assessed the understanding and acceptability of Nueva Vizcaya State University’s (NVSU) amended VMDGCV among electrical engineering stakeholders, including students, teachers, staff, alumni, and parents. Data were collected from 120 purposively chosen respondents using a descriptive-quantitative methodology and a validated survey. Two principal dimensions—awareness and acceptability—were examined using descriptive statistics and ANOVA. The findings indicated that respondents exhibited modest awareness (mean = 3.28, SD = 0.69), with the university's developmental objectives for cultivating competent and values-driven graduates earning the greatest acknowledgment (mean = 3.60). The average acceptance rating was moderate (mean = 3.17, SD = 0.77), indicating overall endorsement of the institution's trajectory. Electrical Engineering students had considerably superior scores compared to other groups in both domains (ANOVA: F = 9.132, p < .05), indicating enhanced engagement via academic exposure. Conversely, instructors, staff, alumni, and parents exhibited diminished levels of familiarity and support. The research emphasizes the need of more effectively integrating institutional ideals across stakeholder interactions. Results demonstrate a moderate level of awareness and acceptability, particularly among students. It is advisable to implement broader communication methods and more inclusive engagement initiatives to improve alignment with institutional objectives and cultivate a unified, mission-oriented academic atmosphere.